Differential responses of coolwater fishes to a whole‐lake reduction of a warmwater thermal guild - Holly S. Embke; Stephen R. Carpenter; T. Douglas Beard Jr.; Giancarlo Coppola; Daniel A. Isermann; Eric J. Pedersen; Andrew L. Rypel; Christopher J. Sullivan; Tyler D. Tunney; M. Jake Vander Zanden (Ecosphere, 2025)
Abstract Climate change is transforming the ecology of lakes at a rapid pace, shifting some lakes toward warmwater‐dominant habitats. As a result, warmwater fishes are increasingly becoming more prevalent in lakes where they already existed, altering the patterning and strength of species interactions. Understanding shifting species interactions (e.g., competition, predation), and the role of lake management in shaping these interactions, will be critical for lake stewardship in response to climate change. Here, we present results from an intensive 5‐year experimental removal of ~285,000 warmwater fishes from a north‐temperate lake. The goal of the experiment was to test whether warmwater fish reduction is effective for rewiring lake food webs to reverse undesirable conditions for coolwater species, leading to increased recruitment and abundance of coolwater fishes. Throughout the experiment, warmwater fishes were resilient to reductions, with biomass declines of 23% averaged across five species. Among coolwater fishes, the top predator walleye showed no biomass response, while yellow perch biomass increased by ~914%. Fish species biomass changes translated to food web shifts, including a yellow perch trophic position decline of 0.4, decreased zooplankton abundances, and increased zoobenthos abundances. Our results highlight differential species responses to a management action aimed at adapting to climate change. Despite similar thermal tolerances, two coolwater species responded differently to removal of warmwater fishes, highlighting the characteristics (e.g., life history strategies, adaptive capacity) that contribute to species resilience. Given the importance of biotic interactions, climate adaptation may need to go beyond a “one‐size‐fits‐all” approach even when species have similar thermal tolerances.